Glymphatic system: a self-purification circulation in brain - Siying Chen; Siying Chen; Huijing Wang; Lini Zhang; Yingying Xi; Yiying Lu; Kailin Yu; Yujie Zhu; Izmailova Regina; Yong Bi; Fang Tong; Fang Tong (Frontiers in Cellular Neuroscience)
The glymphatic system theory introduces a new perspective on fluid flow and homeostasis in the brain. Here, cerebrospinal fluid and interstitial fluid (CSF-ISF) moves from the perivascular spaces (PVS) of arteries to those of veins for drainage. Aquaporin-4 (AQP4) plays a crucial role in driving fluid within the PVS. The impairment to AQP4 is closely linked to the dysfunction of the glymphatic system. The function of the glymphatic system is less active during waking but enhanced during sleep. The efficiency of the glymphatic system decreases with aging. Damage to the glymphatic system will give rise to the development and progression of many brain diseases, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), chronic traumatic encephalopathy (CTE), and vascular dementia (VaD). Here, we reviewed previous research associated with the glymphatic system, including its concepts, principles, and influencing factors. We hypothesize that AQP4 could be a target for the prevention and treatment of certain brain diseases through the regulation on the glymphatic system.